MEASUREMENT DEVICE FOR TESTING PRINTED CIRCUIT BOARD ASSEMBLIES COMING OFF THE PRODUCTION LINE - Friškovec, Nejc; Obreza, Manja; Seme, Sebastijan; Sredenšek, Klemen (Journal of Energy Technology, 2023)
The paper presents an efficient way to evaluate and determine the quality of an assembled printed circuit board coming off the production line. A printed circuit board assembly consists of electronic devices soldered to the printed circuit board, which provides the electrical connections. After assembling the printed circuit board, a function test needs to be performed to guarantee the quality of the product. Usually, the assembly lines are equipped with cameras that detect inaccuracies such as missing components. This level of quality assurance is sometimes not enough, and we need to add another degree of precaution. In addition to camera inspections, electronic measurements must be conducted. The process needs to be automated to provide repeatability and speed. The paper evaluates such a device and presents its advantages, disadvantages, and complexity. The device includes an electrical part that performs the measurements, a mechanical part that consists of a housing and a mounting nest, and a program that supervises the process.